Bioarchaeology of the American Southeast : Approaches to Bridging Health and Identity in the Past - Bailey, Ralph (University of Alabama Press, 2018)
Intro -- Contents -- List of Illustrations -- Foreword / Mary Lucas Powell -- Preface / Shannon Chappell Hodge and Kristrina A. Shuler -- Acknowledgments -- Introduction / Kristrina A. Shuler and Shannon Chappell Hodge -- PART I. CONTEXT AND CULTURE HISTORY IN BIOARCHAEOLOGY -- 1. Biodistance among Four Louisiana Archaeological Sites from the Woodland Period / Steven N. Byers and Rebecca Saunders -- 2. Health in Transition: An Assessment of Nonspecific Pathologies during the Coles Creek Period in the Southern Lower Mississippi Valley / Ginesse A. Listi -- 3. Regional Differences in Caries by Sex and Social Status in Late Prehistoric East Tennessee / Tracy K. Betsinger and Maria Ostendorf Smith -- 4. The End of Prehistory in the Land of Coosa: Oral Health in a Late Mississippian Village / Mark C. Griffin -- PART II. SOCIAL IDENTITIES IN BIOARCHAEOLOGY -- 5. Nonlethal Scalping in the Archaic: Violence, Trophy Taking, and Social Change / Shannon Chappell Hodge -- 6. Warriors, Identity, and Gender: Status and Health at the King Site / Matthew A. Williamson -- 7. Intentional Cranial Shaping: A View from Lake Cormorant and Irby Sites, De Soto County, Mississippi / Della Collins Cook -- 8. Voyageurs in a New World: A French Colonial Cemetery in Nouveau Biloxi / J. Lynn Funkhouser and Barbara Thedy Hester -- 9. A Tale of Two Cemeteries: Bioarchaeology and Cultural Resources Management at the Citadel / Kristrina A. Shuler, Emily Jateff, Eric C. Poplin, Ralph Bailey Jr., Eric Sipes, and Charles F. Philips Jr. -- 10. Skeletal Remains from the School of Anatomy, DeSaussure College, University of South Carolina / William D. Stevens, Carlina de la Cova, Christopher Judge, and Christopher Young -- References Cited -- Contributors -- Index.